Sissy [videorecording (DVD)] - Dee, Aisha, 1993-; Barlow, Hannah; Margheriti, Emily De; Monks, Daniel (RLJE Films, 2023)
"Cecilla (Sissy) and Emma were tween-age BFFs who were going to grow old together and never let anything come between them. That is, until Emma's new friend Alex did just that. When Cecilia became the target of Alex's bullying, it forced Cecilia and Emma apart. Twelve years later, Cecilia is a successful influencer living the dream ... until she runs into Emma for the first time in over a decade, and her world is turned upside down"--Container insert.